Formulasi Gel Ekstrak Metanol Bunga Cempaka Putih (Magnolia alba) sebagai Antijerawat terhadap Bakteri Staphylococcus aureus - Ni Nyoman Yudianti Mendra; Kadek Desy Aryantini; Debby Juliadi (Jurnal Farmasi Indonesia, 2024)
The white champaca flower is an evergreen plant that thrives in Bali, local populations take advantages of its fragrance for ritual purposes and aromatherapy. The antibacterial, antifungal, and antioxidant activity of the white champaca flower (Magnolia alba) are well-known, besides its utility as aromatherapy. These activities were attributed to the presence of secondary metabolites such as flavonoid, tannin, steroid, and saponin. This study aimed to determine the antibacterial activity of methanol extract of Magnolia alba formulated as a gel against Staphylococcus aureus. Gel formulations were prepared using various concentration of extract FI (4%), FII (6%), and FIII (8%). The physical tests included organoleptic, homogeneity, pH, dispersibility, and adhesion test. The antibacterial activity was evaluated using agar well diffusion method, with Clindamycin gel as the positive control. Statistical analysis of the inhibition zone was conducted using a Post Hoc test at a 95% confidence level. The addition of extract in each formula affected its physical properties, particularly the dispersibility. The gel exhibited a spreadability range of 2,67 – 4,22 cm, which fell below the standard 5-7 cm. The gel viscosity increased with a higher concentration of extract, resulting in reduced spreadability of the gel. The Inhibition zone of the sample against S.aureus was observed with an inhibition diameter of 6,33 mm and 11,37 mm for FII and FIII, respectively, compared to the positive control of 22,17 mm. These findings indicate that the methanol extract gel of Magnolia alba can inhibit the growth of S.aureus and has the potential as an anti-acne gel with moderate and strong inhibitory effects. The inhibitory activity of the gel against bacteria increased with a higher concentration of the extract.